Impact of coronavirus pandemic on cancer patients; is it time for ectoine and/or ACE inhibitors? - Eman El-Abd (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2020)
Cancer patients require attention after COVID-19. ACEI and/or ectoine could represent potential adjuvant therapy. Clinical trials are required to investigate this hope to mitigate COVID-19 infectivity and cell invasion.